Effect of Iron Additives on the Microstructure of Hydroxyapatite - Gamal, G. A.; Al-Mufadi, F. A.; Said, A. H. (Engineering, Technology & Applied Science Research, 2013)
In this article, some Fe (III) doped hydroxyapatite samples (FeHAp) were prepared using the wet chemical method. The prepared samples were characterized via the use of X-ray diffraction (XRD) and scanning electron microscopy (SEM). Detailed structural analysis were done by Scherrer and Williamson–Hall plot methods to detect the effect of iron on the structure of hydroxyapatite (HAp). XRD patterns showed that all samples were single phased HAp. Relations between the Fe content and the deformation of the lattice parameters, dislocation density, grain size, microstrain, crystallinity were investigated. The presence of iron in the HAp lattice is found to decrease both the crystal size and the dislocation density. Further results are presented and discussed.